Considerations on recent housing urban project . paris case through the reully, bercy and tolbiac zacs (2008)
The urban transformation of Paris, that took place between the eighties and nineties of Twenty Century, has as one of its principal protagonists the urban residential project. A type of project that is placed in a cultural change opposite to the ideas of the previous urbanism –the modern renovations of the fifties to seventies– which is characterized for: confronting the city transformation upon its own study; giving a new look to the form of the urban traditional values; and, being interested in the obsolete and degraded spaces as opportunity to act. Therefore, the new residential neighborhoods are characterized for answering to these ideas, specifically across the urban and architectural rules with which the project is defined. In the article I identify some of these rules as instruments for the definition of a new urban space according to the city re-composition, and raise some questions about the role of the tradition and the innovation in the urban development intervention of the contemporary city, analyzing the cases of the ZAC Reuilly, Bercy and Tolbiac.